To the understanding of the mechanism of formation of point mutations in DNA - Kryachko, E.S.; Volkov, S.N. (Reports of the National Academy of Sciences of Ukraine, 2018)
A mechanism for the point mutations formation in DNA is proposed, which takes into account the fluctuating appearance of the complementary pairs preopened by water molecules in the double helix. In the framework of the density functional method, possible transitions of protons in the preopened A · T pair are analyzed, and their structures and energies are calculated. It has been shown that the formation of preopened base pairs in the DNA catalyzes the stability of the non-regular forms of nucleic bases, which can serve as the source of a point mutation. The estimated probability of such mutation occurrence in DNA (10−10—10−11) explains the known experimental data.